Hospital-based intervention is rarely needed for children with low-grade blunt abdominal solid organ injury: An analysis of the Trauma Quality Improvement Program registry. Issue 4 (October 2021) - Evans, Lauren L.; Williams, Regan F.; Jin, Chengshi; Plumblee, Leah; Naik-Mathuria, Bindi; Streck, Christian J.; Jensen, Aaron R.
Abstract : BACKGROUND: Children with low-grade blunt solid organ injury (SOI) have historically been admitted to an inpatient setting for monitoring, but the evidence supporting the necessity of this practice is lacking. The purpose of this study was to quantify the frequency and timing of intervention for hemorrhage and to describe hospital-based resource utilization for low-grade SOI in the absence of other major injuries (OMIs). METHODS: A cohort of children (aged <16 years) with blunt American Association for the Surgery of Trauma grade 1 or 2 SOI from the American College of Surgeons Trauma Quality Improvement Program registry (2007–2017) was analyzed. Children were excluded if they had confounding factors associated with intervention for hemorrhage (comorbidities, OMIs, or extra-abdominal surgical procedures). Outcomes included frequency and timing of intervention (laparotomy, angiography, or transfusion) for hemorrhage, as well as hospital-based resource utilization. RESULTS: A total of 1, 019 children were identified with low-grade blunt SOI and no OMIs. Nine hundred eighty-six (96.8%) of these children were admitted to an inpatient unit. Admitted children with low-grade SOI had a median length-of-stay of 2 days and a 23.9% intensive care unit admission rate. Only 1.7% (n = 17) of patients with low-grade SOI underwent an intervention, with the median time to intervention being the first hospital day. No child who underwent angiography was transfused or had an abnormal initial ED shock index. CONCLUSION: Children with low-grade SOI are routinely admitted to the hospital and often to the intensive care unit but rarely undergo hospital-based intervention. The most common intervention was angiography, with questionable indications in this cohort. These data question the need for inpatient admission for low-grade SOI and suggest that discharge from the emergency room may be safe. Prospective investigation into granular risk factors to identify the rare patient needing hospital-based intervention is needed, as is validation of the safety of ambulatory management. LEVEL OF EVIDENCE: Prognostic and epidemiological, level III. Abstract : Supplemental digital content is available in the text.